Pengaruh Tampilan Web dan Harga terhadap Keputusan Pembelian pada E-Commerce Shopee di Indonesia dengan Kepercayaan sebagai Variabel Intervening - Della Nurlista; Mirza Murni; Nara Pristiwa (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
Shopee has become one of the most popular e-commerce platforms in Indonesia due to its attractive website design, competitive pricing, and high level of consumer trust, despite facing competition and challenges in maintaining service quality. Factors such as attractive website design, easy navigation, price promotions, and transaction security have been shown to significantly influence consumer purchasing decisions, especially following the increase in e-commerce usage during the pandemic. Based on initial findings and various issues faced by users, this study aims to analyze the influence of website appearance and price on purchasing decisions on Shopee e-commerce in Indonesia, with trust as an intervening variable. This study used a quantitative approach with a survey method by distributing questionnaires to 96 Shopee user respondents selected using a purposive sampling technique. Data analysis was conducted using path analysis and the Sobel test to examine the direct and indirect effects between variables. The results showed that website appearance and price significantly influence consumer trust. Website appearance and trust also significantly influence purchasing decisions. However, price does not directly influence purchasing decisions; however, trust is shown to mediate the effect of price on purchasing decisions. This finding implies that building consumer trust is a key factor in improving purchasing decisions, especially in the context of competitive pricing while still being trusted by consumers.